La privación de las exequias eclesiásticas en el Código de Derecho Canónico de 1983. (2015)
The article presents the canonical legislation about ecclesiastical burial. It exposes the canonical provisions concerning the fact of a christian death, referring also to the liturgical ones. The thesis was aimed at comparing the rules contained in the two codes of canon law. This document refers particularly to cases in which the church grants or denies the ecclesiastical burial with special reference to 1983 Code of Canon Law. It was taken into account the legislation issued after the code of 1917, which influenced the formation of the current regulation. The issue has not been exhausted; there are some pastoral issues conceding the relatives who must face a situation when the church deprives the funeral to their deceased relative.